Engineering recombinant newcastle disease virus with pro-apoptotic gene to enhance oncolysis in selected colorectal cancer cells - Kalyanasundram, Jeevanathan (2020)
Anticancer therapy manipulating oncolytic Newcastle disease virus (NDV) has been reported to show exciting prospects. Since NDV is an avian virus, it is generally cleared by the human immune system, thus making it safe for humans. However, this also reduces viral replication in cancer cells, therefore compromising its full oncolytic potential. The cloning of pro-apoptotic gene such as apoptin into the NDV genome may produce a recombinant NDV with enhanced oncolytic ability which could result in higher tumour killing before being cleared by the immune system. In this study, development of local NDV strain AF2240 as a vector for pro-apoptotic, apoptin transgene delivery into tumour was explored in order to improve AF2240 oncolytic ability. The main objective of the study is to develop a recombinant AF2240 virus armed with pro-apoptotic transgene, capable of higher oncolysis and increased potency by using a selection of colorectal cancer cells as model. Colorectal cancer cells such as HT29, SW620 and CaCo-2 was selected due to their heterogeneity in supressing pro-apoptotic and anti-viral signalling. A recombinant anti-genomic plasmid, pOLTV5(rAF-ApHGy) was constructed by inserting the apoptin gene into the M and F intergenic region within AF2240 anti-genome. Recombinant AF2240 harbouring apoptin transgene, rAF-ApHGy was successfully recovered from the transfection of the anti-genomic plasmid into BSRT7/5 cells and propagated in embryonated chicken eggs. The recovered rAF-ApHGy virus stably harboured the apoptin transgene through 5 egg passages. The replication kinetics was found to be similar to that of the parental AF2240 strain. The apoptin gene was also detected to be expressed in rAF-ApHGy-infected HT29, SW620 and Caco-2 colorectal cells. The cytotoxicity of rAF-ApHGy was detected to be enhanced compared to wildtype strain AF2240 among infected HT29, SW620 and Caco-2 colorectal cells through MTT assay and flow cytometry analysis. Flow cytometric analysis of infected HT29 showed rAF-ApHGy to result in 26.58%, 34.29% and 31.47% more cell death population compared to AF2240 infection at 24, 48 and 72 h.p.i. Similarly, infection of SW620 cells also revealed rAF-ApHGy resulted in 3.05%, 18.74% and 13.37% more cell death population compared to wildtype AF2240 infection at 24, 48 and 72 h.p.i. Infection of Caco-2 cells with rAF-ApHGy was detected to induce 4.94%, 14.08% and 9.02% more cell death compared to AF2240 infection at 24, 48 and 72 h.p.i. These findings were further corroborated by MTT analysis. Virus infection of HT29 particularly, showed increased population entering into necrotic phase which were determined to be secondary necrosis as appose to necroptosis through RIP-PARP-Caspase 8 cell signalling analysis. The latter also revealed increased cleaved Bax in the rAF-ApHGy infected HT29 cells compared to wildtype strain AF2240, indicating the enhanced oncolytic ability of rAF-ApHGy. Based on these findings, it can be concluded that AF2240 can be genetically modified for pro-apoptotic transgene delivery without compromising virus stability. The enhanced oncolytic ability of rAF-ApHGy highlights the potential of this recombinant strain AF2240 to result in higher oncolysis compared to its wildtype counterpart, before being cleared by patient’s immune response during oncovirotherapy.